Photoacoustic Imaging Guided Near‐Infrared Photothermal Therapy Using Highly Water‐Dispersible Single‐Walled Carbon Nanohorns as Theranostic Agents. (26th August 2014) - Chen, Daiqin; Wang, Chao; Nie, Xin; Li, Shumu; Li, Ruimin; Guan, Mirong; Liu, Zhuang; Chen, Chunying; Wang, Chunru; Shu, Chunying; Wan, Lijun
<x xml:space="preserve">Abstract</x> The poly(maleic anhydride‐alt‐1‐octadecene‐poly(ethylene glycol)) (C18PMH‐PEG) modified single‐walled carbon nanohorns (SWNHs) are designed with high stability and biocompatibility. The as‐prepared SWNHs/C18PMH‐PEG not only can serve as an excellent photothermal agent but also can be used as a promising photoacoustic imaging (PAI) agent both in vitro and in vivo due to its strong absorption in the near infrared (NIR) region. The PAI result reveals that the SWNHs/C18PMH‐PEG possesses ultra long blood circulation time and can significantly be accumulated at the tumor site through the enhanced penetration and retention (EPR) effect. The maximum accumulation of SWNHs/C18PMH‐PEG at tumor site could be achieved at the time point of 24 h after intravenous injection, which is considered to be the optimal time for the 808 nm laser treatment. The subsequent photothermal ablation of tumors can be achieved without triggering any side effects. Therefore, a PAI guided PTT platform based on SWNHs is proposed and highlights the potential theranostic application for biomedical uses.